Pengaruh Jarak Tanam dan Dosis Pupuk Kandang Terhadap Pertumbuhan dan Produksi Tanaman Kubis Bunga Putih (Brassica oleracea var. botrytis L. subvar. cauliflora DC). - Hamidah Hamidah (Agrifarm : Jurnal Ilmu Pertanian, 2012)
Dose Effect of Plant Spacing and Manure on Growth and Production of White Flower Cabbage (Brassica oleracea var. Botrytis L. subvar. Cauliflora DC). Under the guidance of Rustam baraq Noor and Hamida. Order to determine the effect of plant spacing and doses of manure and interaction on the growth and yield of the White Flower Cabbage (Brassica oleracea var. Botrytis L. subvar. Cauliflora DC). Research carried out for 4 months, from the month from June to September 2011. The study was conducted in land practices Bapeltan UPTB Sempaja Samarinda. Research arranged in a randomized block design (RBD) with 3 × 4 factorial analysis and repeated 3 times. The first factor is the spacing of (K), which consists of three levels, namely: k1 (spacing of 60 cm × 50 cm), k2 (spacing of 60 cm × 60 cm) and k3 (spacing of 60 cm × 70 cm). The second factor is the dose of chicken manure (F) which consists of 4 levels, namely: f0 (Control), f1 (1.5 kg dose of chicken manure / m2), f2 (dose 2.0 kg chicken manure / m2 and f3 (dose 2.5 kg chicken manure / m2). The results showed the best treatment plant spacing on k2 (spacing of 60 cm × 60 cm). The treatment dose of the best chicken manure on f2 (dose 2.0 kg chicken manure / m2). The combination of treatment and dose spacing of the best chicken manure on k2f2 {(spacing of 60 cm × 60 cm); (dose 2.0 kg of chicken manure / m2)}.